Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content:Developing the performance of public education departments in the Kingdom of Saudi Arabia in light of strategic managementMs. Mashael Asir Al-Otaibi., Ms. Jawaher Khalid Al-Yousef. ,Ms. Haifa Khalif Al-MaalawiThe reality of applying entrepreneurial leadership in secondary schools in Jeddah from the teachers' point of viewMr. Abdulrahman Hamid Al-SalaThe Impact of The Digital Story in the Development of some Life Skills among Children  with Autism in A Human Development Center in Al-QassimMs. Faten Marzouq MeznanThe Role of Artificial Intelligence Applications in Developing Vocational Education;  A Future Vision for Professional TrainingMs. Asma Thabet M. Alorfi., Ms. Maha Ouda Awad AlharbiMindfulness as a predictor of impulsive behavior among female high school students  in Jeddah, Saudi ArabiaMs. Nojod Melfi AlharbiChallenges Related to Children Faced by Kindergarten Teachers of Children with Autism Spectrum Disorder in Improving Their Quality of LifeMs. Rajaa Ebrahim NassarThe Perceptions of Yemeni Universities Students towards Practical Training  and Internships  in Translation ProgramsMs. Azhar Abdulrahman Raweh, Prof. Mohammad Abdu Al-Mekhlafi
Keywords: Journal of Educational and Psychological Sciences